The Behavior of Rice and Egg Traders in Manarap Market, Kertak Hanyar District, Banjar District Perspective of Islamic Business Ethics - Ilham Fajar; Faqih El Wafa El Wafa (IAIN Palopo, 2023)
This research is motivated by the experience of the community who considers that the behavior of rice and egg traders in the Manarap market is contrary to sharia business ethics. The purpose of this study was to determine the business ethics behavior of rice and egg traders in the Manarap market in terms of Islamic business ethics. This research is a field research with a qualitative approach, the number of traders studied is 10 people. Data collection used observation techniques and direct interviews with informants, namely rice and egg traders. The collected data were analyzed based on Islamic business ethics theory. Through a Qualitative Approach, the following findings are obtained: first, the business of rice and egg traders in Manarap Market has implemented Islamic business ethical behavior, which can be seen from several attitudes: honesty, trustworthiness, fairness, sincerity, diligence and hard work, not badmouthing other traders, all rice and egg traders in Manarap Market but in the attitude of working harder there are 2 people who work harder than other traders because they also sell elsewhere. Second, traders who apply Islamic business ethics as a whole, out of 10 informants, only 2 or 20%.